The Determinant Factors of Performance of Provincial Governments in Indonesia - Hadi Jauhari; Evada Dewata (Universitas Negeri Malang, 2019)
The focus of this research study includes the influence of local government actions, leverage, weaknesses in the internal control system, and audit findings (Republic of Indonesia Supreme Audit Agency) both partially and simultaneously on the implementation performance of provincial governments in Indonesia for the 2015-2016 period. Partially, the size of local government has a positive and significant influence on the performance of local governments. Leverage, weaknesses in the internal control system and findings of the Board of Audit of the Republic of Indonesia do not have a significant effect on the performance of local governments. Simultaneously, the size of local government, leverage, weaknesses of the internal control system, and findings of the Board of Audit of the Republic of Indonesia have a significant influence on the performance of local governments with a contribution of the R square effect of 21.29. %.